Impact of spar-nacelle-blade coupling on the edgewise response of floating offshore wind turbines - DINH, VAN NGUYEN; BASU, BISWAJIT (Techno-Press, 2013)
The impact of spar-nacelle-blade coupling on edgewise dynamic responses of spar-type floating wind turbines (S-FOWT) is investigated in this paper. Currently, this coupling is not considered explicitly by researchers. First of all, a coupled model of edgewise vibration of the S-FOWT considering the aerodynamic properties of the blade, variable mass and stiffness per unit length, gravity, the interactions among the blades, nacelle, spar and mooring system, the hydrodynamic effects, the restoring moment and the buoyancy force is proposed. The aerodynamic loads are combined of a steady wind (including the wind shear) and turbulence. Each blade is modeled as a cantilever beam vibrating in its fundamental mode. The mooring cables are modeled using an extended quasi-static method. The hydrodynamic effects calculated by using Morison?s equation and strip theory consist of added mass, fluid inertia and viscous drag forces. The random sea state is simulated by superimposing a number of linear regular waves. The model shows that the vibration of the blades, nacelle, tower, and spar are coupled in all degrees of freedom and in all inertial, dissipative and elastic components. An uncoupled model of the S-FOWT is then formulated in which the blades and the nacelle are not coupled with the spar vibration. A 5MW S-FOWT is analyzed by using the two proposed models. In the no-wave sea, the coupling is found to contribute to spar responses only. When the wave loading is considered, the coupling is significant for the responses of both the nacelle and the spar.
PUBLISHED
Keywords: wind energy; floating offshore wind turbine; blade-nacelle-spar couping; hydrodynamic effects; Morison's equation